We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
113
3
avatar

If f(x)=5x-12, find a value for x so that f^-1(x)=f(x+1).

After solving this, please show me how to solve other inverse function problems because I am very confused!!!

Thanks in advance laugh

 Feb 11, 2019
 #1
avatar+5172 
+1

\(\text{we find the inverse by setting }y=f(x)\\ \text{solving for }x \text{ in terms of }y \text{, and then substituting }y \to x\)

 

\(f(x)=5x-12\\ y=5x-12\\ x = \dfrac{y+12}{5}\\ f^{-1}(x) = \dfrac{x+12}{5}\)

 

\(f^{-1}(x) = f(x+1)\\ \dfrac{x+12}{5} = 5(x+1)-12\\ x+12 = 25(x+1)-60\\ 24x = 47\\ x = \dfrac{47}{24}\)

.
 Feb 11, 2019
 #2
avatar+22315 
+6

If f(x)=5x-12, find a value for x so that f^-1(x)=f(x+1).

 

\(\begin{array}{|rclcrcl|} \hline f\Big(f^-1(x)\Big) &=& x & | & \quad f^-1(x)&=& f(x+1) \\ f\Big(f(x+1)\Big) &=& x & | & \quad f(x+1) &=& 5(x+1) - 12\\ && & | & \quad &=& 5x - 7 \\ f\Big(5x - 7)\Big) &=& x \\ 5(5x-7)-12 &=& x \\ 25x-35-12 &=& x \\ 24x &=& 47 \\ \mathbf{x} & \mathbf{=} & \mathbf{\dfrac{47}{24}} \\ \hline \end{array}\)

 

laugh

 Feb 11, 2019
 #3
avatar+7531 
+1

First find f-1(x).

\(x = 5f^{-1}(x)-12\\ f^{-1}(x) = \dfrac{x+12}{5}\).

Equate this to f(x+1), which is 5(x+1)-12.

\(\dfrac{x+12}{5}=5x-7\\ x+12 = 25x-35\\ 24x=47\\ x = \dfrac{47}{24}\)

.
 Feb 14, 2019

8 Online Users

avatar